Parental Overprotection and Youth Anger Expression: The Mediating Role of Experiential Avoidance - Şahin, Ayşe; Soylu , Dilek (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The objective of this study was to examine the mediating role of experiential avoidance in the relationship between parental overprotection and anger expression among adolescents and young adults.Methods and Materials: This study used a descriptive–correlational design with a sample of 400 adolescents and young adults from Turkey, determined using the Krejcie and Morgan sampling table. Participants completed the State–Trait Anger Expression Inventory-2 (STAXI-2) to assess anger expression, the Acceptance and Action Questionnaire-II (AAQ-II) to measure experiential avoidance, and the Parental Bonding Instrument (PBI) to assess parental overprotection. Data were analyzed using SPSS-27 for descriptive and correlational analyses, and AMOS-21 for structural equation modeling (SEM).Findings: The results indicated that parental overprotection was positively correlated with both experiential avoidance (r = .42, p < .001) and anger expression (r = .39, p < .001). Experiential avoidance was also positively correlated with anger expression (r = .46, p < .001). SEM analyses revealed that parental overprotection significantly predicted experiential avoidance (b = 0.47, β = .42, p < .001), and experiential avoidance significantly predicted anger expression (b = 0.62, β = .44, p < .001). The direct path from parental overprotection to anger expression was significant (b = 0.28, β = .21, p < .001), and the indirect effect through experiential avoidance was also significant (b = 0.29, β = .18, p < .001).Conclusion: The findings suggest that experiential avoidance partially mediates the relationship between parental overprotection and anger expression, highlighting avoidance as a key transdiagnostic mechanism.